2007
DOI: 10.1007/s00464-007-9440-4
|View full text |Cite
|
Sign up to set email alerts
|

Liver histology alterations during carbon dioxide pneumoperitoneum in a porcine model

Abstract: Histomorphologic changes occurred, indicating liver tissue injury during CO(2) pneumoperitoneum at an intraabdominal pressure of 12 mmHg in the porcine model. Portal vein flow increased, and hepatic artery flow decreased, whereas aortic flow remained relatively unaffected in this experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
(47 reference statements)
0
16
0
2
Order By: Relevance
“…Previous studies have described mainly three methods of measuring liver blood flow: (1) measuring the blood flow of the portal vein and hepatic artery by placing the probe directly on the vessels, (2) measuring the hepatic venous flow using transesophageal Doppler echocardiography, and (3) measuring the velocity and number of red blood cells by using a laser Doppler flowmeter on the liver surface. In studies in which the vessel blood flow was measured directly, the blood flow in the portal vein and hepatic artery was found to decrease or remain unchanged under pneumoperitoneum [12][13][14][15]. In a previous study that used transesophageal Doppler echocardiography, it was found that the blood flow in the hepatic vein significantly increased during pneumoperitoneum in humans [16].…”
Section: Histological Findings In the Livermentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have described mainly three methods of measuring liver blood flow: (1) measuring the blood flow of the portal vein and hepatic artery by placing the probe directly on the vessels, (2) measuring the hepatic venous flow using transesophageal Doppler echocardiography, and (3) measuring the velocity and number of red blood cells by using a laser Doppler flowmeter on the liver surface. In studies in which the vessel blood flow was measured directly, the blood flow in the portal vein and hepatic artery was found to decrease or remain unchanged under pneumoperitoneum [12][13][14][15]. In a previous study that used transesophageal Doppler echocardiography, it was found that the blood flow in the hepatic vein significantly increased during pneumoperitoneum in humans [16].…”
Section: Histological Findings In the Livermentioning
confidence: 94%
“…Several studies have reported that the levels of liver enzymes increase in patients undergoing laparoscopic surgery [7][8][9]; however, unaltered liver function has been also reported [10,11]. Furthermore, various studies have reported different changes in the hepatic blood flow during pneumoperitoneum [12][13][14][15][16]. The differences in the duration of pneumoperitoneum and intra-abdominal pressure during pneumoperitoneum between the experimental conditions and clinical settings may result in these different outcomes [10].…”
mentioning
confidence: 96%
“…The current study found liver histomorphology impairment after both CO 2 PP and BDL. In HE stained liver samples, OJ and PP each caused sinusoidal congestion and vacuolization in hepatocytes, but this was more severe in the PP-only group 3 than in the OJ-only group 2 and PP applied jaundiced subjects (group 4), indicating that ischemia or anoxia occurs during CO 2 PP [34]. These changes indicate hepatic tissue damage.…”
Section: Discussionmentioning
confidence: 73%
“…Schachtrupp et al found low-grade paracentral hypoxic necrosis and moderate sinusoidal leukocyte infiltration after 24 h of CO 2 PP in a porcine model [33]. A study by Alexakis et al showed a time course increase in portal inflammation, intralobular inflammation, edema, sinusoidal dilation, sinusoidal hyperemia, centrilobular dilation, centrilobular hyperemia, pericentrilobular ischemia, and focal lytic necrosis scores in a porcine model [34]. On the other hand, as early as 2 to 3 h after BDL, patches of hepatic necrosis are evident [35].…”
Section: Discussionmentioning
confidence: 94%
“…Large-animal model histologic analysis for randomized minimally invasive surgery studies is not routine. The grading system was modified from Alexakis et al 13 and relied on the expertise of the clinical veterinary pathologist.…”
mentioning
confidence: 99%